2021
DOI: 10.1021/acs.jpcc.0c10792
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing CO Coverage on Rough Copper Electrodes: Effect of the Partial Pressure of CO and Electrolyte Anions (pH) on Selectivity toward Ethylene

Abstract: The conversion of the initial intermediate CO in the electrochemical reduction reaction of CO 2 on the surface of oxide-derived Cu electrodes has been investigated as a function of partial pressure and pH, manipulated by the composition of the electrolyte. We show that in inert gas, an increase in partial pressure of CO results in a continuous increase in Faradaic efficiency (FE) for ethylene, at various potentials ranging from −0.7 to −1.1 V versus RHE, with the highest FE of ∼28% obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…In addition to catalyst innovations, parameters associated with the electrolyte (ion identity, pH, ionic strength) and process conditions (gaseous reactant fugacity, temperature) change the catalytic performance. The electrolyte cations likely perturb the interfacial electric field near the electrode and thereby energy levels of reaction intermediates. In some studies, larger alkali metal cations promoted the electrochemical CO–CO coupling and enhanced C 2+ formation on polycrystalline Cu (pc-Cu) surfaces via electrocatalytic CO (2) reduction. , In contrast, the influence of electrolyte anions on electrocatalytic performance remains controversial. ,,, For example, a study employing surface-enhanced IR absorption spectroscopy (SEIRAS) revealed that the identity of anions changed the CO chemisorption energy on Cu electrodes and in turn the electrocatalytic performance of CO (2) reduction, especially the specifically adsorbing anions (Cl – and PO 4 3– ) . On the contrary, another study demonstrated that product distributions of CO electroreduction over the pc-Cu were insensitive to identifying electrolyte anions in the presence of phosphate, carbonate, or perchlorate .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to catalyst innovations, parameters associated with the electrolyte (ion identity, pH, ionic strength) and process conditions (gaseous reactant fugacity, temperature) change the catalytic performance. The electrolyte cations likely perturb the interfacial electric field near the electrode and thereby energy levels of reaction intermediates. In some studies, larger alkali metal cations promoted the electrochemical CO–CO coupling and enhanced C 2+ formation on polycrystalline Cu (pc-Cu) surfaces via electrocatalytic CO (2) reduction. , In contrast, the influence of electrolyte anions on electrocatalytic performance remains controversial. ,,, For example, a study employing surface-enhanced IR absorption spectroscopy (SEIRAS) revealed that the identity of anions changed the CO chemisorption energy on Cu electrodes and in turn the electrocatalytic performance of CO (2) reduction, especially the specifically adsorbing anions (Cl – and PO 4 3– ) . On the contrary, another study demonstrated that product distributions of CO electroreduction over the pc-Cu were insensitive to identifying electrolyte anions in the presence of phosphate, carbonate, or perchlorate .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that a lowered coverage of *CO facilitated *CO protonation for Cu-based catalysts. 19,38–42…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that a lowered coverage of *CO facilitated *CO protonation for Cu-based catalysts. 19,[38][39][40][41][42] We performed DFT calculations with the Cu (111) facet as the model slab to explore the impact of BDT on *CO coverage and CO 2 RR selectivity. 10 The BDT molecule rested on the Cu (111) slab in its energy-optimal form (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The local pH near the electrode plays an important role in the *CO/*H coverage, which determines whether *CO subsequently undergoes dimerization or hydrogenation. At lower pH values, *CO prefers to form CH 4 in the presence of abundant *H. At higher pH, where *H is scarce and *CO coverage is high, ethylene formation dominates over ethane formation [158]. As the rate of OH − production depends on the applied potential, it is necessary to probe the local pH near the electrode under operational conditions.…”
Section: Local Microenvironment Effectsmentioning
confidence: 99%